STUDI KASUS: PERAWATAN PAYUDARA POSTPARTUM UNTUK MELANCARKAN PRODUKSI ASI - Widy Markosia Wabula; Fasiha Fasiha (Poltekkes Kemenkes Maluku, 2022)
Breastfeeding is a natural process, but often mothers do not succeed in breastfeeding or stop breastfeeding early. Therefore, mothers need help so that the breastfeeding process is more successful. Breast care is an action to care for the breasts, especially during the puerperium (breastfeeding period) to expedite the release of breast milk. Breast care is very important during pregnancy to breastfeeding. This is because the breast is the only producer of breast milk which is the staple food for newborns, so it must be done as early as possible. The assessment in this case study was conducted on a P3A0 mother. From the results of the examination, it was found that the breasts looked tense, the nipple areola looked dirty and the milk had not come out. From the results of further studies, the mother complained of lack of sleep because her baby often cried. Based on these complaints, midwifery care was carried out, namely postpartum breast care, guiding positions and breastfeeding techniques that were good and correct and KIE regarding nutrition in postpartum mothers. Routine breast care can accelerate milk production. The role of the midwife to support the success of breastfeeding in postpartum.